Investigating infection management and antimicrobial stewardship in surgery: a qualitative study from India and South Africa. (October 2021) - Singh, Sanjeev; Mendelson, Marc; Surendran, Surya; Bonaconsa, Candice; Mbamalu, Oluchi; Nampoothiri, Vrinda; Boutall, Adam; Hampton, Mark; Dhar, Puneet; Pennel, Tim; Tarrant, Carolyn; Leather, Andy; et al.
Abstract: Objectives: To investigate the drivers for infection management and antimicrobial stewardship (AMS) across high-infection-risk surgical pathways. Methods: A qualitative study—ethnographic observation of clinical practices, patient case studies, and face-to-face interviews with healthcare professionals (HCPs) and patients—was conducted across cardiovascular and thoracic and gastrointestinal surgical pathways in South Africa (SA) and India. Aided by Nvivo 11 software, data were coded and analysed until saturation was reached. The multiple modes of enquiry enabled cross-validation and triangulation of findings. Results: Between July 2018 and August 2019, data were gathered from 190 hours of non-participant observations (138 India, 72 SA), interviews with HCPs (44 India, 61 SA), patients (six India, eight SA), and case studies (four India, two SA). Across the surgical pathway, multiple barriers impede effective infection management and AMS. The existing implicit roles of HCPs (including nurses and senior surgeons) are overlooked as interventions target junior doctors, bypassing the opportunity for integrating infection-related care across the surgical team. Critically, the ownership of decisions remains with the operating surgeons, and entrenched hierarchies restrict the inclusion of other HCPs in decision-making. The structural foundations to enable staff to change their behaviours and participate in infection-related surgical care are lacking. Conclusions: Identifying the implicit existing HCP roles in infection management is critical and will facilitate the development of effective and transparent processes across the surgical team for optimized care. Applying a framework approach that includes nurse leadership, empowering pharmacists and engaging surgical leads, is essential for integrated AMS and infection-related care.